Strategi Penguatan Kelembagaan Kelompok Tani untuk Meningkatkan Daya Saing Agribisnis Paprika (Studi Kasus di Kelompok Tani Dewa Family) - Jafaruddin, Nurhana; Diana, Tungga Buana; Oktavia, Henita Fajar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Paprika is a high-economic-value horticultural commodity with increasing demand in modern retail and culinary industries, yet its fulfillment is often hindered by supply continuity and quality standard issues. This study aims to analyze the institutional conditions and competitiveness of paprika agribusiness, as well as to formulate institutional strengthening strategies for the Dewa Family Farmer Group. The method used is descriptive qualitative with a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats) to identify internal and external factors. The results indicate that Dewa Family possesses internal strengths in the form of 29 greenhouses with modern technology and strong retail partnership networks (Hero, Superindo, Lottemart), but still faces weaknesses in skilled labor capacity and unstandardized cultivation management. The formulated institutional strengthening strategies include optimizing production technology, enhancing human resource competence through training, and implementing strict SOPs to ensure supply stability and competitiveness in both domestic and export markets.